Chondronecrosis with osteomyelitis in broilers: further defining lameness-inducing models with wire or litter flooring to evaluate protection with organic trace minerals - Alrubaye, Adnan A.K. (Poult Sci, 2020)
The feed additive Availa-ZMC was investigated for the ability to reduce lameness in broilers using 2 alternative models for inducing lameness. The mixture of organic trace minerals was effective in reducing lameness by 20% in the wire flooring model and 25% in the litter flooring model with the bacterial challenge. Lameness in both models is overwhelmingly attributable to bacterial chondronecrosis with osteomyelitis. The reduction in lameness was associated, at least in part, with enhanced intestinal barrier integrity mediated by elevated expression of tight junction proteins and stimulation of bactericidal killing of adherent peripheral blood monocytes obtained from the birds treated with Availa-ZMC. Lameness is a major animal welfare concern in broiler production. The wire flooring model and litter flooring model with the bacterial challenge are effective models for evaluation of management strategies for mitigating infectious causes of lameness.